PENENTUAN BEASISWA DENGAN MENGGUNAKAN PERHITUNGAN TECHNIQUE FOR OTHERS REFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) - Umar Mansyuri; Hamid Al Jufri; Yasin Efendi (Jurnal Ilmiah Sistem Informasi, 2022)
TOPSIS or Technique For Others Reference by Similarity to Ideal Solution is a multi-criteria decision-making method which has the concept of selecting the best alternative based on the shortest distance from the positive ideal solution and the farthest distance from the negative ideal solution. The purpose of this study is to apply the TOPSIS method which can assist in determining the priority of scholarships for students by considering various predetermined criteria. There are four criteria used in this study, namely: average grade, class rank, number of siblings, parental income, and number of achievements. The system development method used is the modified waterfall method, with the stages carried out in the form of analysis, design, implementation and testing. The system that has been built is a system that can make it easier to determine scholarship recipients